THRESHOLD SENSITIVE WIRELESS SENSOR NETWORK WITH IMPROVED LEACH - kajla, Raghuveer; mandal, Sandip (IJRDO -Journal of Computer Science Engineering, 2015)
The foremost difference between the WSN andthe traditional wireless networks is that sensors areextremely sensitive to energy consumption. Energysaving is the crucial issue in designing the wirelesssensor networks. LEACH Protocol plays an importantrole in response to the uneven energy distribution thatis caused by the randomness of cluster heads forming.LEACH adopts a hierarchical and adaptive approachto organize the network into a set of clusters, managedby selected CHs . Further, the proposed systemimproves the parent network into the most prominentwireless sensor network’s routing protocol “LEACH”as TSWSN with Improved LEACH by introducingefficient cluster head replacement scheme and efficienttransmitting power levels. The implementation of theclustering algorithms including the proposed advancedLEACH protocol is done using MATLAB.Keywords-Threshold value(tv), sensing value(sv),Threshold sensitive wireless sensor network(TSWSN),Base station(BS) , Clustering algorithms.